Adventive Larval Parasitoids Reconstruct Their Close Association with Spotted-Wing Drosophila in the Invaded North American Range. Issue 4 (20th May 2022) - Abram, Paul K; Franklin, Michelle T; Hueppelsheuser, Tracy; Carrillo, Juli; Grove, Emily; Eraso, Paula; Acheampong, Susanna; Keery, Laura; Girod, Pierre; Tsuruda, Matt; Clausen, Martina; Buffington, Matthew L; et al.
Abstract: Two species of larval parasitoids of the globally invasive fruit pest, Drosophila suzukii (Diptera: Drosophilidae), Leptopilina japonica, and Ganaspis brasiliensis (both Hymenoptera: Figitidae), were detected in British Columbia, Canada in 2016 and 2019, respectively. Both are presumed to have been unintentionally introduced from Asia; however, the extent of their establishment across different habitats with diverse host plants used by D. suzukii was unclear. In addition, there was no knowledge of the temporal dynamics of parasitism of D. suzukii by these two parasitoids. To address these gaps, we repeatedly sampled the fruits of known host plants of D. suzukii over the entire 2020 growing season in British Columbia. We documented the presence of L. japonica and G. brasiliensis and estimated the apparent percentage of D. suzukii parasitized among host plant species. Across a large region of southwestern British Columbia, both L. japonica and G. brasiliensis were found to be very common across a variety of mostly unmanaged habitats over the entire course of the season (May–October) in the fruits of most host plants known to host D. suzukii larvae. Parasitism of D. suzukii was variable (0–66% percent parasitism) and appeared to be time-structured. Our study demonstrates that the close association between the two larval parasitoids and D. suzukii that exists in Asia has evidently been reconstructed in North America, resulting in the highest parasitism levels of D. suzukii yet recorded outside of its area of origin.